Dynamic response evaluation of inclined pavements with interface shear. (4th August 2014) - Siddharthan, Raj; Sebaaly, Peter E.; Zafir, Zia
Pavement performance data reveal that the upward sloping pavements deteriorate much faster than downward sloping pavements. This paper documents the influence of the pavement–tyre interface shear stress and vehicle speed on the response of sloping pavements. An efficient "finite layer" moving load model has been used to predict the pavement strain response in terms of the principal shear strain and longitudinal tensile strain in the AC layer and the vertical compressive strain on top of the sub–grade. The impact of the strains' magnitudes on the fatigue and rutting performance of flexible pavements is also presented. In the analyses, the AC layer and the unbound materials were assumed viscoelastic and linear elastic, respectively. The study reveals that, since the increase in the speed of the vehicle decreases the pavement–tyre interface shear stress and increases the rate of loading, it plays a major role in decreasing the rate of pavement deterioration. For example, there is only about a 6% increase in the maximum principal shear strain, between the upward and downward sloping pavements if the speed of the vehicle remains constant. However, if the speeds of the vehicle on the upward and downward sloping pavements are 30 and 80 km/hr respectively, then the difference in has been computed to be as much as 70%.